Human Capıtal and Talent Management in the Halal Ecosystem: A Systematıc and TCCM-Based Systematıc Revıew - Satriyo, Cindy Charisma; Bungin, Burhan; Sembiring, Murpin Joshua; Mahsun, Moch (APMBA (Asia Pacific Management and Business Application), 2026)
A comprehensive understanding of human development is essential for strengthening talent management, as it ensures the alignment of individual capabilities with organizational and strategic needs. This study employs bibliometric methods alongside the Theory–Context–Characteristics–Method (TCCM) framework to examine developments in human capital and talent management within the global halal ecosystem. A total of 86 publications from 2010 to 2025 were analyzed using R Biblioshiny. The study evaluates methodological trends, conceptual patterns, and existing research gaps. The findings reveal a significant surge in publications after 2020, highlighting the growing strategic importance of halal human resources in the context of digital transformation and global sustainability goals. The dominant theoretical foundations are the Resource-Based View (RBV) and Human Capital Theory; however, integration with Islamic ethical perspectives remains limited. Three major thematic clusters emerge: ethical leadership and Sharia-compliant governance; digital innovation and talent readiness; and human capital development. Based on these insights, the study proposes a Halal Human Capital Excellence Framework that integrates legitimacy, ethics, and digital human capital. It further recommends multi-level and cross-regional empirical studies to validate the proposed model and strengthen both theoretical and policy contributions to future halal talent development.